EXAMINATION OF PERSONALITY DIMENSIONS DETERMINING THE CAREER MOTIVATION OF TRAINEE TEACHERS - Szilvia BORBELY; David OLAH (Cluj University Press, 2021)
In our research, we are interested in how personality dimensions can influence the career choices of students entering teacher education and the extent to which sport appears as a preference variable in the strength of career motivation factors. There is a shortage of teachers, and the prestige of teachers is low (Borbély, 2016). The contradictory social situation of teachers is characterised by the incongruence of knowledge and material benefits related to the profession and prestige (Fónai, 2014). The teaching career is preferred among people with repressive personality traits (Figula, 2000). In our study, we used the Eysenck personality test and the Factors Influencing Teaching Choice Scale career motivation test. Our sample is given by 244 trainee teachers participating in the teacher training of the University of Nyíregyháza, whose average age is 21.93 years. The sample includes physical education trainee teachers (56.6%) and non-physical education trainee teachers (43.4%) of the undivided teacher training. Students majoring in physical education are more willing to take risks, are more sociable, more extroverted than non-physical education trainee teachers, and are more emotionally stable and respond more calmly to various stimuli. The risk-taking personality trait has a negative effect on career motivation and increases the secondary career nature of the teaching profession. Impulsivity shows a positive relationship with personal usefulness, secondary career path, and social influence, while social conformity shows a positive relationship with the beauty of the teaching profession and social usefulness. Our studies provide a picture of the motivation of the physical education trainee teachers and other trainee teachers, as well as the differences between the groups. It helped to explore the factors influencing teacher career motivation and the degree of correlation. Our research proved that during the time spent in training, the perspective of trainee teachers about the teaching career changes, and their motivation, and thus the attraction of the career, decreases.